Identification of The Characteristics of Menoreh Coffee and Cocoa Potential and Its Contribution to Tourism - Anjar Dwi Astono; Herwin Herwin (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study intends to obtain an effective and efficient strategy in the development of agri-tourism areas based on community empowerment. This study used a qualitative approach with six sources consisting of group leaders of coffee and cocoa farmers as well as tourism enthusiasts and representatives from the government. The analysis used in this research is VRIO framework and content analysist. The findings in this study indicate that there is still a very large potential for tourism, especially related to non-mainstream tourism such as cultural tourism, educational tourism and also religion tourism. Increasing the role of the government can be in the form of making regulations that favor farmers and entrepreneurs of coffee and cocoa commodities as well as initiating triple helix cooperation between farmers, government and investors.